Structure and flexibility of the tropomyosin overlap junction - Li, Xiaochuan (Edward); Orzechowski, Marek; Lehman, William; Fischer, Stefan (Biochemical and biophysical research communications, 2014)
To be effective as a gatekeeper regulating the access of binding proteins to the actin filament, adjacent tropomyosin molecules associate head-to-tail to form a continuous super-helical cable running along the filament surface. Chimeric head-to-tail structures have been solved by NMR and X-ray crystallography for N- and C-terminal segments of smooth and striated muscle tropomyosin spliced onto non-native coiled-coil forming peptides. The resulting 4-helix complexes have a tight coiled-coil N-terminus inserted into a separated pair of C-terminal helices, with some helical unfolding of the terminal chains in the striated muscle peptides. These overlap complexes are distinctly curved, much more so than elsewhere along the superhelical tropomyosin cable. To verify whether the non-native protein adducts (needed to stabilize the coiled-coil chimeras) perturb the overlap, we carried out Molecular Dynamics simulations of head-to-tail structures having only native tropomyosin sequences. We observe that the splayed chains all refold and become helical. Significantly, the curvature of both the smooth and the striated muscle overlap domain is reduced and becomes comparable to that of the rest of the tropomyosin cable. Moreover, the measured flexibility across the junction is small. This and the reduced curvature ensure that the super-helical cable matches the contours of F-actin without manifesting localized kinking and excessive flexibility, thus enabling the high degree of cooperativity in the regulation of myosin accessibility to actin filaments.